Strategi Pemulihan Citra Partai Politik: Kasus Partai Demokrat - Masduki Masduki (Universitas Islam Indonesia, 2014)
Academic studies and practical application of political communication strategy gained a right momentum in the current political landscape of contemporary Indonesian since the political reform in 1998. The need to build a reputation for political parties and politicians in the electoral political system requires relevant scientific devices, in the form of a communication strategy that is capable of forming and taking care of the individual and organizational image in the midst of instant culture in political practice. The strong influence of mass media is used to manipulate flow of political information in the midst of political literacy crisis among Indonesian communicity at large. This paper outlines the phenomenon of confidence crisis in the political parties, especially the Democratic Party –the party that was born in the post New Order regime. After striken by corruption cases, Democrat’s position dropped and need to restore its image and reputation. In this paper, Democrat is chosen as an example because it represents the political party profiles that experienced a leap and led by Soesilo Bambang Yudhoyono, the successful president in defend his position for two periods. Borrowing image restoration theory developed by William Benoit (1995), this paper presents and analyzes the publication activities of the Democratic Party in the 2014 election that can be involved as image restoration as anti-corruption political party. This paper will also be enriched recommendations for similar action in the future.